Co-adjoint orbits of compact Lie groups and generalized stereographic projection - Skrypnik, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We generalize the notion of stereographic projection to the case of an arbitrary compact Lie group and find the explicit form of the local complex parametrization of an orbit of the corresponding group.